Using a Diffraction Grid to Measure the Wavelength of a POF Laser - Sri Purwaningsih; Neneng Lestari; Edi Yuversa; Cicyn Riantoni (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The research has been carried out to determine the wavelength of the POF laser using a diffraction grating. The diffraction grating used consists of three kinds of grid constants, namely 100 lines/mm, 300 lines/mm, and 600 lines/mm. Furthermore, the variation of the distance between the grid and the screen with a length of 40 cm, 60 cm, and 90 cm is carried out. The results showed that the wavelength of the POF laser light was between 664.07 nm-728.31 nm and the red monochromatic light source obtained the interference pattern of light on the screen as well as red monochromatic light. Based on the results of the research, it can be proven that the wavelength obtained from the use of a diffraction grating to measure the wavelength of the red laser is close to the wavelength value of 664.07 nm.